Strategy and human resources management - Butler, John E., 1946- (South-Western, 1991)
Introduction. Human resources management. Expanding the strategy-making concept. A profit-generation theory of strategic human resources management. Human resources and the anatomy of strategic planning. Strategic staffing. Strategy and the performance-evaluation process...